(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The issue of competitiveness has been relevant for many years. The growth of business activity and the emergence of strategic surprises currently lead to an aggravation of the need to find a promising direction for the development of the enterprise. The main reason for the great interest of many scientists and practitioners in this issue is that competitiveness has a significant impact on the achievement of the main strategic goal of the enterprise, namely the increase in sales of goods, services and, accordingly, the maximum possible increase in profits.